Pemanfaatan Platform Kahoot Sebagai Media Pembelajaran Interaktif - Rafnis Rafnis (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2018)
Conducive and enjoyable learning in the industrial revolution 4.0 makes a change in learning styles in the learning process. Teachers are required to follow an interactive digital learning process. Fun and non-boring learning is one of the challenges for instructors and Learning Technology Developers to innovate in learning. Interactive learning innovation in this study is to use Kahoot as an interactive learning media based on game based learning that emphasizes the active participation learning styles of all students. One of the Kahoot Platforms used was the use of online quizzes, where students immediately reflected their answers online and Kahoot recorded all the activities of students that could become assessment resume materials for teachers. This study aims to find out how the Kahoot application is feasible in the learning process by understanding students' responses to this application. This study uses a Qualitative method by using Kahoot in the learning of 22 students who take the Business Feasibility System course in the Faculty of Economics Study Program, Campus II Payakumbuh Andalas University. This study obtained a final percentage of 85% with Very Interesting criteria. It was concluded that the use of the Kahoot platform used was very suitable to be used in creating interactive and fun learning.Keywords: Industrial Revolution 4.0, Kahoot, Qualitative